2018
DOI: 10.1136/archdischild-2018-314873
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the usability of paediatric weight estimation methods: a simulation study

Abstract: In this exploratory study under psychological stress none of the methods of weight estimation were free from error. Reference tables were the fastest method and also had the largest errors and should be designed to minimise the risk of picking errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Some of the most commonly used weight estimation methods include formulas based on age, the Broselow Pediatric Emergency Tape, and newer dual length and habitus-based systems, such as the Mercy Method and the Pediatric Advanced Weight Prediction in the Emergency Room, Extra-large/Extra-long (PAWPER XL) Tape. Some of these methodologies, such as agebased formulas, have already been shown to be inaccurate in previous studies, but the underlying causes have not been well-studied [5][6]. Other techniques, such as the PAWPER XL Tape, have been shown to be accurate in some studies [7][8][9] but could still potentially be improved, especially as other studies have shown inconsistent accuracy in obese populations [10][11], primarily as a result of inaccurate habitus assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most commonly used weight estimation methods include formulas based on age, the Broselow Pediatric Emergency Tape, and newer dual length and habitus-based systems, such as the Mercy Method and the Pediatric Advanced Weight Prediction in the Emergency Room, Extra-large/Extra-long (PAWPER XL) Tape. Some of these methodologies, such as agebased formulas, have already been shown to be inaccurate in previous studies, but the underlying causes have not been well-studied [5][6]. Other techniques, such as the PAWPER XL Tape, have been shown to be accurate in some studies [7][8][9] but could still potentially be improved, especially as other studies have shown inconsistent accuracy in obese populations [10][11], primarily as a result of inaccurate habitus assessment.…”
Section: Introductionmentioning
confidence: 99%
“…This findings in this study can also not be generalized to age-based formula systems: although virtual studies may be able to evaluate the potential accuracy of these formulas, not enough work has been done to even speculate meaningfully on the impact of human and patient factor errors on the use of age-formulas in emergencies. Furthermore, current evidence does not support the use of age-formulas in terms of both accuracy and usability [5] , [19] .…”
Section: Discussionmentioning
confidence: 74%
“…Virtual weight estimation studies and those conducted in non-clinical (or non-simulated clinical) conditions may not provide an accurate indication of the usability of a weight estimation system or its accuracy under adverse conditions. In a recent meta-analysis, only seven of the 150 weight estimation studies included were conducted in real or simulated paediatric emergencies with two further articles published subsequently [2] , [4] , [5] . This means that there is very little evidence on the actual functioning of weight estimation systems when exposed to human and patient factor errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations